The Impact of Asymmetric Decentralization on Public Health: A Synthetic Control Analysis of Special Autonomy in Aceh and Papua - Chalil, Tengku Munawar (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — This study introduces a novel methodological framework utilizing the synthetic control method to assess the causal impact of Indonesia’s special autonomy policies in Aceh and Papua on health outcomes, explicitly accounting for unobserved confounders (e.g., economic and social trends) that earlier before‑after comparisons overlooked. Research Objectives — The paper aims to quantify the impact of Aceh’s and Papua’s special autonomy status on key health indicators—immunization coverage, birth attendance by health workers, and morbidity rates—by comparing each province to its constructed synthetic counterpart. The policy impacts were observed by comparing the changes with synthetical Aceh and Papua, which do not receive any special autonomy intervention. Research Methods — The study employs the synthetic control method by constructing weighted composites of non‑autonomous provinces as counterfactuals, estimating differences in health outcomes in Aceh and Papua before and after the introduction of special autonomy. Empirical Results — For Aceh, the performance of the morbidity rate is no better than that of its comparable synthetic control. Moreover, Aceh performs better than its synthetic control for the health provision indicators, specifically birth attendances by health workers and immunization coverage. For Papua, the performance of health outcomes such as morbidity rates, birth attendance by health workers, and immunization coverage is worse than that of its comparable synthetic peers. Implications — The result implication should support the continuity of asymmetric decentralization for Aceh and Papua, together with the sustainability of special autonomy grants for Aceh and Papua, as the government takes the momentum of revision for special autonomy law for Aceh and Papua.